Expanding Emerging Markets through Vocational Skill Acquisition: The Role of E-Learning Initiatives - Israel Olukayode Adebowale; Olusegun Micheal Ige (Eastasouth Institute, 2026)
This paper examined vocational skill acquisition and development from the perspective of e-learning. It explores how e-learning facilitates the dissemination of vocational education by enabling easy access to educational content, promoting interactive and collaborative learning experiences, and allowing for the reuse and adaptation of instructional materials. The advent of the internet has made it increasingly possible for individuals to simultaneously learn, grow, and adapt in pursuit of personal and economic advancement. Furthermore, the paper discusses key concepts, processes, operational frameworks, and the benefits of e-learning in the context of human capital development, particularly in emerging economies where access to traditional education and training may be limited. It is suggested that computer literacy programmed be further entrenched in educational system right from the early stages so that the learners will have an early introduction into the computer world which will facilitate online programmmes orientation.